2015
DOI: 10.1016/j.yjmcc.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation mediates Cx43 reduction caused by electrical stimulation

Abstract: Communication between cardiomyocytes depends upon Gap Junctions (GJ). Previous studies have demonstrated that electrical stimulation induces GJ remodeling and modifies histone acetylases (HAT) and deacetylases (HDAC) activities, although these two results have not been linked. The aim of this work was to establish whether electrical stimulation modulates GJ-mediated cardiac cell-cell communication by acetylation-dependent mechanisms. Field stimulation of HL-1 cardiomyocytes at 0.5 Hz for 24 hours significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Cx43 is the main constituent of gap junctions, and participates in cell-to-cell signaling ( 10 , 11 ). Studies have found that the expression and distribution of Cx43 would be changed after myocardial infarction ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 is the main constituent of gap junctions, and participates in cell-to-cell signaling ( 10 , 11 ). Studies have found that the expression and distribution of Cx43 would be changed after myocardial infarction ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…PES also affects epigenetics through acetylation, histone modifications, alteration of the structural organization of chromatin, demethylation, as well as affecting RNA. PES downregulates histone deacetylase activities in HL-1 cells, with a significant reduction in Cx43 expression and cellcell communication (Meraviglia et al, 2015). PES can also reversibly downregulate the activity of histone 1 kinase in pig oocytes (Leal and Liu, 1998).…”
Section: Intracellular Components and Organellesmentioning
confidence: 98%
“…Electrical stimulation causes rat muscle dysfunction by altering miRNA-related signaling pathways 30 . Also, electrical stimulation modulates the gap junction-mediated cardiac cell-cell communication by regulating histone acetylase and deacetylase activities 16 . Chromatin structures were changed in BlCa cells exposed to ROS, and high levels of ROS increased H3K9me3 expression in human BlCa tissues 31 .…”
Section: Figure 1 Effects Of Electrofusion On Rabbit Scnt Embryos (A)mentioning
confidence: 99%
“…Also, abnormal epigenetic reprogramming occurs in a large proportion of cloned embryos, and this impedes improvement in SCNT efficiency 1,9 . Electrostimulation also regulates the epigenetic state in somatic cells; however, there are few reports on the effect of electrostimulation on the epigenetic state of embryos 16,17 . In this study, we optimized the electrofusion procedure, and studied its effects on SCNT embryos, oxidative stress, epigenetic state and ER stress.…”
mentioning
confidence: 99%